(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
CRB 8 Digital Vol. 5, n. 1 (2012) Link de acesso ao número http://revista.crb8.org.br/index.php/crb8digital/issue/view/9